Answer: B. 4
Step-by-step explanation:
First, I did the equation out.
Second, I simply it all the way through.
Third, to get 4
<em>The answer is 25.12 exactly</em>
Answer:
z = 83 / (- c + 6 - t)
Step-by-step explanation:
Given:
-cz+ 6z = tz + 83
z=?
-cz+ 6z = tz + 83
Collect like terms
-cz+ 6z - tz = 83
Factorize
z(- c + 6 - t) = 83
Divide both sides by (- c + 6 - t)
z(- c + 6 - t) / (- c + 6 - t) = 83 / (- c + 6 - t)
z = 83 / (- c + 6 - t)
Answer:
P=length of each of the 4 pieces
(8' - 0.25')/4=P
Step-by-step explanation:
P=length of each of the 4 pieces
(8' - 0.25')/4=P
80 I believe hopefully it’s correct